Gelatinization properties of native starches and their Naegeli dextrins - Campanha, Raquel Bombarda [UNESP]; Landi Franco, Celia Maria [UNESP] (Springer, 2011)
Cassava, potato, sweet potato, and Peruvian carrot starches were hydrolyzed with 15% v/v sulfuric acid solution for up to 30 days. Naegeli dextrins obtained from 1, 3, 6, 12, and 30 days were evaluated using differential scanning calorimeter (DSC) and scanning electron microscopy (SEM). Two phases of hydrolysis were found. The first phase was attributed to faster degradation of amorphous areas of granules, whereas the second phase corresponded to slower degradation of crystalline regions. Peruvian carrot starch was the most susceptible to acid, whereas potato and sweet potato starches were the most resistant. From DSC, it was observed a progressive reduction in peak height and a broadening of peaks with increasing hydrolysis time. The peaks shifted to higher temperatures. Onset temperature decreased on first day of hydrolysis for cassava and Peruvian carrot starches, and on third day for potato and sweet potato. Enthalpy decreased during first stage of hydrolysis in cassava and Peruvian carrot starches, and during second phase, it reduced in all starches. SEM showed that the granule surfaces were degraded by erosion on the first day of treatment, followed by degradation of amorphous areas. on third day, potato and sweet potato starches still displayed some granules almost intact, whereas cassava and Peruvian carrot starch granules were totally degraded, confirming their high susceptibility to acid attack. on sixth day of hydrolysis, starch granules had faceted structures, characteristic of crystalline material. The effect that acid hydrolysis had on thermal properties of starches depended on both hydrolysis stage and starch source.
Keywords: Starch; Acid hydrolysis; Gelatinization properties; Naegeli dextrin